Revalidation of Synonymy between Nesotriatoma flavida and N. bruneri (He¬miptera, Reduviidae, Triatominae) - Oscar Páez-Rondón; Fernando Otálora-Luna; Elis Aldana (Tehran University of Medical Sciences, 2017)
Background: We analyzed the external morphology and the external male genitalia of specimens of Nesotriatoma flavida of a laboratory colony founded with specimens from Guanahacabiles in Pinar del Río Province in the west of Cuba in 1980. This species was at first identified as different from N. bruneri and then later considered synonymous. Methods: We proposed to revise the morphological characters with which these species were considered as different and then later synonymous, such as the fossula spongiosa or spongy grooves, length of the first antenna segment, relationship length of eye to interocular distance, the form of the phallosome, phallosome support, and the endosome processes. Results: The results of the analyses of these characters in the specimens of our colony, and of the corresponding works where the separation and synonymy of these species has been proposed, allow us to sustain the revalidation of the synonymy between N. flavida and N. bruneri. Conclusion: Based on the body external morphology and the male external genitalia of N. flavida it is concluded that N. flavida and N. bruneri are synonymous species.